DETERMINACIÓN DE LOS RECURSOS ENERGÉTICOS QUE CUBREN LAS NECESIDADES ALIMENTICIAS EN SISTEMAS DE DEHESA1 DETERMINATION (Archivos de Zootecnia, 1996)
Dehesas are farming systems that covers with their own resources agreat deal of cattle food needs. However. the use and contribution of these resources haven"t a uniform distribution between the diferent stock species. This paper deals with an analytical case study of characteristic dehesas of SW Badajoz (Spain), where the factors that influence the use of grazing resources have been determinated. The analyzed dehesas cover up to 73 p.100 of food needs for ruminants, but only 47 p.100 for Iberian pig. The knowledge of food energetic flows is a solid starting point to analyze the management and the sustainable use of dehesa resources.